Barley residual of a malt factory as a substitute of corn for pigs - Bellaver, Claudio; Fialho, Elias Tadeu; Protas, José Fernando da Silva; Leh, Gerald (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to determine the best level of corn by barley substitution in diets for pigs during growing and finishing period. The level of 0%, 25%, 50%, 75% and 100% substitution were compared using 120 Landrace x Large White pigs, with average initial and final weights of 22.63 kg ±0.40 kg and 96.59 kg ± 1.25 kg, respectively. Positive significant linear effects (P
Keywords: feedstuffs; barley; alternative feeds; energy; Hordeum vulgare